2020
DOI: 10.1093/intimm/dxaa008
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of new blood-vessel formation and proliferative heterogeneity of endothelial cells

Abstract: The vast blood-vessel network of the circulatory system is crucial for maintaining bodily homeostasis, delivering essential molecules and blood cells, and removing waste products. Blood-vessel dysfunction and dysregulation of new blood-vessel formation are related to the onset and progression of many diseases including cancer, ischemic disease, inflammation and immune disorders. Endothelial cells (ECs) are fundamental components of blood vessels and their proliferation is essential for new vessel formation, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
113
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(121 citation statements)
references
References 146 publications
4
113
1
3
Order By: Relevance
“…In this stage, VEGFR2, or KDR, is the earliest and specific marker. Fibroblast growth factor 2 (FGF2) and BMP4 were reported to initiate the specification of the mesoderm and differentiation toward ECs [48]. In the present study, we found that BMP9 up-regulates the expression of KDR at the early stage of osteogenesis in the ectopic bone formation model, which indicates that BMP9 could trigger the process of vasculogenesis.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…In this stage, VEGFR2, or KDR, is the earliest and specific marker. Fibroblast growth factor 2 (FGF2) and BMP4 were reported to initiate the specification of the mesoderm and differentiation toward ECs [48]. In the present study, we found that BMP9 up-regulates the expression of KDR at the early stage of osteogenesis in the ectopic bone formation model, which indicates that BMP9 could trigger the process of vasculogenesis.…”
Section: Discussionsupporting
confidence: 52%
“…Recently, the blood vessel formation process was identified as two stages [48][49][50]. The first stage is vasculogenesis, when mesodermal precursor cells undergo angioblasts differentiation toward ECs.…”
Section: Discussionmentioning
confidence: 99%
“…Embryonal vasculogenesis represents one of the earliest events during organogenesis, as it starts already during gastrulation [50,51]. Vasculogenesis consists in the differentiation, expansion, and assembly of endothelial precursors into a functional blood vessel [49,52]. Vascular development in the embryo is initiated by mesodermal cells, also referred to as hemangioblasts, which migrate into the yolk sac, to form cellular aggregates known as blood islands.…”
Section: Vasculogenesismentioning
confidence: 99%
“…The network of blood vessels expands via two main mechanisms: vasculogenesis is de novo formation of blood vessels, and angiogenesis is sprouting or splitting of existing blood vessels (83). Sprouting angiogenesis occurs in five steps: (A) After action of angiogenic growth factor (e.g., vascular endothelial growth factor, VEGF) on a quiescent blood vessel, there is (B) degradation of the capillary basement membrane followed by (C) EC proliferation and (D) selection of tip and stalk cells.…”
Section: Role Of Tlrs In Blood Vessel Formation and Extensionmentioning
confidence: 99%